Masters and servants : cultures of empire in the Tropics - Lowrie, Claire (Studies in imperialism (Manchester, England), 2016)
'Masters and Servants' explores the politics of colonial mastery and domestic servitude in the neighbouring British colonies of Singapore and Darwin. Through an exploration of master-servant relationships within British, white Australian and Chinese homes, this text illustrates the centrality of the domestic realm to the colonial project. It is a comparative history of domestic service and British colonialism in the tropics, and highlights the important role which 'houseboys' played in colonial households in the tropics and the common preference for Chinese 'houseboys' throughout Southeast Asia.